Continuous Regional Anesthesia Before Surgical Peripheral Sympathectomy in a Patient With Severe Digital Necrosis Associated With Raynaud's Phenomenon and Scleroderma. Issue 4 (1st July 2003) - Greengrass, Roy A.; Feinglass, Neil G.; Murray, Peter M.; Trigg, Stephen D.
Abstract : Background and Objective: Digital ischemia and necrosis caused by Raynaud's phenomenon in patients with connective tissue diseases may not respond to medical therapy and may have major adverse effects on quality of life. We describe the use of continuous ambulatory regional anesthesia for diagnosis and treatment before peripheral sympathectomy in a patient with secondary Raynaud's phenomenon. Case Report: A 55-year-old man with progressive systemic sclerosis and secondary Raynaud's phenomenon presented with severe pain and digital necrosis that were refractory to maximal medical treatment and thoracic sympathectomy. Continuous ambulatory regional analgesia increased digital temperature from 32.3°C at baseline to 34.4°C after 80 minutes. An increase in digital flow was documented by Doppler ultrasound measurements made ventrally at the point of greatest pulsation of the radial artery. Subsequent peripheral sympathectomy resulted in restoration of nutrient flow with healing of ulcers and alleviation of pain. Conclusions: Continuous ambulatory regional anesthesia appears effective as a treatment bridge for vasospasm and ischemia associated with secondary Raynaud's phenomenon. The enhancement of peripheral blood flow achieved with the regional anesthetic technique suggests that surgical peripheral sympathectomy may provide long-term benefits.